Living with Nature, Cherishing Language Indigenous Knowledges in the Americas Through History - Olko, Justyna; Radding, Cynthia (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the deep connections between environment, language, and cultural integrity, with a focus on Indigenous peoples from early modern times to the present. It illustrates the close integration of nature and culture through historical processes of environmental change in North, Central, and South America and the nurturing of local knowledge through ancestral languages and oral traditions. This volume fills a unique space by bringing together the issues of environment, language and cultural integrity in Latin American historical and cultural spheres. It explores the reciprocal and necessary relations between language/culture and environment; how they can lead to sustainable practices; how environmental knowledge and sustainable practices toward the environment are reflected in local languages, local sources and local socio-cultural practices. The book combines interdisciplinary methods and initiates a dialogue among scientifically trained scholars and local communities to compare their perspectives on well-being in remote and recent historical periods and it will be of interest to students and scholars in fields including sociolinguistics, (ethno)history, linguistic anthropology, cultural studies and cultural anthropology, environmental studies and Indigenous/minority studies. Justyna Olko is Professor in the Faculty of "Artes Liberales" at the University of Warsaw, Poland and director of its Center for Research and Practice in Cultural Continuity. She specializes in Indigenous history, sociolinguistics, contact linguistics, language endangerment and revitalization of ethnic minority and Indigenous languages, multilingualism as well as decolonizing research practices. Cynthia Radding is Gussenhoven Distinguished Professor of History and Latin American Studies at The University of North Carolina, USA. She researches the imperial borderlands of the Ibero-American empires, emphasizing the role of indigenouspeoples and other colonized groups in shaping those borderlands, transforming their landscapes, and producing colonial societies.